Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1002/eji.200838970
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory role of DC‐derived osteopontin in systemic allergen sensitization

Abstract: Osteopontin (OPN) is a secreted phosphoglycoprotein with a wide range of functions, and is involved in various pathophysiological conditions. However, the role of OPN in IgE and Th2-associated allergic responses remains incompletely defined. The aim of this study was to elucidate the role of OPN in systemic allergen sensitization in mice. When compared with OPN 1/1 mice, significantly increased levels of OVA-induced IgE were found in OPN À/À mice.OPN À/À DC demonstrated an increased capacity to enhance Th2 cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Based on our finding that rOPN inhibits allergen sensitization (production of allergen-specific IgE antibody) [25], OPN itself may be a promising therapeutic target for the treatment of IgE-mediated allergic diseases. In this context, increases in OPN levels, as shown in our previous reports [20,21], may play a role in the efficacy of allergen immunotherapy.…”
Section: Therapeutic Strategies Against Allergy and Asthma Based On Omentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our finding that rOPN inhibits allergen sensitization (production of allergen-specific IgE antibody) [25], OPN itself may be a promising therapeutic target for the treatment of IgE-mediated allergic diseases. In this context, increases in OPN levels, as shown in our previous reports [20,21], may play a role in the efficacy of allergen immunotherapy.…”
Section: Therapeutic Strategies Against Allergy and Asthma Based On Omentioning
confidence: 99%
“…To elucidate the role of OPN in IgE-mediated allergic responses, we compared the ovalbumin (OVA)-induced specific IgE levels between wild-type (WT) and OPNdeficient (OPN À/À ) mice, and found that OPN À/À mice had significantly higher levels of OVA-induced IgE and systemic Th2 than WT mice [25]. In addition, treatment with recombinant OPN (rOPN) during intraperitoneal injection of OVA suppressed OVA-specific IgE production in WT and OPN À/À mice.…”
Section: Osteopontin Modulates Immunoglobulin E-mediated Allergic Resmentioning
confidence: 99%
“…Such sOPN-dependent suppression of DC migration may be mediated by, at least in part, downregulation of CCR7 in the DCs [54, 55], which enhances migration of mature DCs into regional LNs. Another study demonstrated that sOPN plays a regulatory role in systemic allergen sensitization by inducing IL-12 expression by DCs [56]. In contrast to OPN’s function in acute phase of AHR [53, 56], OPN appears to play a role as an inducer of AHR and lung remodeling in chronic phase by multiple allergen challenges [57].…”
Section: Opn and Immune-related Diseasesmentioning
confidence: 99%
“…DCs were generated from mouse bone marrow (BM) using an established protocol [18,19]. Briefly, mouse BM was obtained from the femurs and tibiae.…”
Section: Methodsmentioning
confidence: 99%